New design of tuned vibration absorber for wide frequency range application - Ghazali, Mohd Hafiz (2015)
Vibrations are undesirable in machines and structures because they increased stresses, energy losses, cause added wear, increase bearing loads, induce fatigue, create passenger discomfort in vehicles. Uncontrolled vibrations can leave a bad impression to the machine, structure, and human. Vibration on machine can damage the equipment, decrease the machine lifetime and also causing the safety factor problems. In this research, a tuned vibration absorber (TVA) was chosen to be studied where the amount of vibration reduced was determined through finite element analysis (FEA) and validated with the experimental result. A actual scale of tuned vibration absorber was developed and applied on the structure to reduce the vibration. It is expected that by using the new design of tuned vibration absorber, the vibration of the structure can be reduced extensively. The objective of this project is to design and fabricate a newly tuned vibration absorber (TVA) that address a broad frequency range of application, light in weight, small-scale and suitable for mobile purposes. In order to achieve this aim, the preliminary design analysis was performed using finite element analysis before validated by experimental test. There are two design proposed in this study which is design 1 and design 2. The design concept was designed by using SolidWorks® and simulation test was done in this phase as well. From these two design, only one design was selected to be manufactured and tested. Design 1 was selected to be manufactured due to its performance in finite element analysis. DEWEsoft-201 were used as an equipment in experimental phase where the equipment will measure and generate graph data based on vibration performance. This experiment done several times according to the mass distance which is from 0 to 40 sequently. All the data were validated to ensure that the data from the finite element analysis and experimental are matched or even better. The data obtained shows good matched where the data gained are almost the same. The new vibration absorber has a weight of 620.6 kg and it is suitable for mobile purposes.